Characterization of clustered bacteriocin-type signal domain protein genes in Treponema denticola - Nukaga, Tomoyuki; Kokubu, Eitoyo; Okamoto-Shibayama, Kazuko; Kikuchi, Yuichiro; Furusawa, Masahiro; Muramatsu, Takashi; Ishihara, Kazuyuki (Frontiers in Dental Medicine, 2025)
BackgroundPeriodontitis is caused by the dysbiosis of subgingival plaque, and Treponema denticola is the pathogen associated with this disease. Bacteriocins are involved in interbacterial competition during dysbiosis. In our previous study, three potential bacteriocin ABC transporter genes (tepA1-B1, tepA2-B2, and tepA3-B3) of T. denticola were investigated. Upstream of tepA1-B1, three genes annotated as bacteriocin-type signal domain proteins are located. However, the role of these proteins in T. denticola remains unclear. In the present study, these bacteriocin-type signal domain proteins were characterized to elucidate their putative roles in T. denticola.MethodsGene clusters surrounding bacteriocin-type signal domain protein genes were compared in silico. The expression of proteins and transporters was evaluated using real-time quantitative reverse transcription PCR (qRT-PCR). Bacteriocin-type signal domain proteins were detected using immunoblot analysis. The expression of bacteriocin-like proteins was investigated by co-culturing with Treponema vincentii.ResultsThe DNA sequences of the bacteriocin-type signal domain protein genes and upstream lipoprotein genes were highly conserved. Expression of the bacteriocin-type signal domain protein and tepA1 was slightly higher in the mid-log phase than in the stationary phase and was reduced upon co-culture with T. vincentii. Bacteriocin ABC transporter gene tepA1 was expressed independently of tepA2 and tepA3. Immunoblot analysis detected bacteriocin-like proteins in culture supernatants. However, bactericidal activity was not detected in the culture supernatant of T. denticola.ConclusionThree tandem lipoprotein-bacteriocin-type signal domain protein genes may have originated from duplication. Bacteriocin-type signal domain proteins are expressed under unstimulated conditions and are secreted by T. denticola cells.